Smoking and Physical Activity Explain the Increased Mortality Risk Following Marital Separation and Divorce: Evidence From the English Longitudinal Study of Ageing. Issue 3 (23rd May 2018) - Bourassa, Kyle J; Ruiz, John M; Sbarra, David A
Abstract: Background: Marital separation and divorce are associated with an increased risk of early mortality, but the specific biobehavioral pathways that explain this association remain largely unknown. Purpose: This study sought to identify the putative psychological, behavioral, and biomarker variables that can help explain the association of being separated or divorced and increased risk for early mortality. Methods: Using data from the English Longitudinal Study of Ageing, a representative community sample of aging adults ( N = 5, 786), we examined the association of marital status and life satisfaction, health behaviors measured 2 years later, biomarkers measured 4 years later, and mortality outcomes from the subsequent 4 years. Results: Consistent with prior literature, older adults who were separated/divorced evidenced greater risk of mortality relative to those in intact marriages over the study period, OR = 1.46, 95% CI [1.15, 1.86]. Marital status was associated with lower levels of life satisfaction, β = −0.22 [−0.25, −0.19] and greater likelihood of smoking 2 years later β = 0.17 [0.13, 0.21]. Lower life satisfaction predicted less frequent physical activity 2 years later, β = 0.07 [0.03, 0.10]. Smoking, but not physical activity, predicted poorer lung functioning 2 years later, β = −0.43 [−0.51, −0.35], and poorer lung function predicted increased likelihood of mortality over the following 4 years, β = −0.15 [−0.27, −0.03]. There was a significant total indirect effect of marital status on mortality through these psychological, behavioral, and biomarker variables, β = 0.03 [0.01, 0.05], which fully explained this mortality risk. Conclusions: For separated/divorced adults, differences in life satisfaction predict health behaviors associated with poorer long-term lung function, and these intermediate variables help explain the association between marital dissolution and increased risk of earlier mortality. Abstract : In a large sample of older adults, the risk for early mortality associated with marital separation and divorce is fully accounted for by psychological wellbeing, physical activity, and smoking.